Efficacy of Dosages of the Embryonic Stimulant Preparation for Preventing of Postpartum Complications in Cows - Hamidullovich Baimishev, Murat; Petrovich Eremin, Sergey; Baltukhanovich Baimishev, Hamidulla; Aleksandrovna Baimisheva, Svetlana; Nasibulovich Khakimov, Ismagil; ., . (International Journal of Engineering and Technology, 2018)
The research was aimed at determining the optimal dosage of "STEMB" (Embryonic Stimulant) for preventing delivery and postnatal complications, for which purpose 4 groups of 20 cows in each were formed. During the experiment, the animals in the studied groups were in similar feeding and keeping conditions, dry matter in the diet amounted to 44.95%. The animals in the experimental groups received "STEMB" subcutaneously three times in the 30 days period before delivery with the interval of 7 days in the following dosages: the first experimental group received 0.05 ml per 1 kg of live weight; the second experimental group received 0.075 ml per 1 kg of live weight; the third experimental group received 0.10 ml per 1 kg of live weight; the cows in the reference group did not receive the preparation. It has been determined that the dosage of "STEMB" equal to 0.075 ml per 1 kg of live weight prevents postpartum complications, shortens the labor and the postpartum period. The obtained data may be used for developing the reference criteria of using "STEMB" for correcting the reproductive function and preventing complications during delivery and postnatal complications.Â Â Â